Policy Uncertainty and Innovation: Evidence from Initial Public Offering Interventions in China - Cong, Lin William; Howell, Sabrina T. (Management Science, 2021)
Public equity is an important source of risk capital, especially in China. The Chinese government has occasionally suspended IPOs, exposing firms already approved to IPO to indeterminate listing delays. The temporary bar on going public increases uncertainty about access to public markets for affected firms. We show that suspension-induced delay reduces corporate innovation activity both during the delay and for years after listing. Negative effects on tangible investment and positive effects on leverage are temporary, consistent with financial constraints during the suspensions being resolved after listing. Our results suggest that predictable, well-functioning IPO markets are important for firm value creation. They demonstrate that corporate innovation is cumulative and is negatively affected by policy uncertainty. This paper was accepted by Gustavo Manso, finance.